The Effect of Authentic Leadership in Increasing Employees' Psychological Capital and Creativity Moderated by Job Satisfaction - HAR, M Senen; Sadikin, Ali (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aims to determine the effect of authentic leadership in increasing employees psychological capital and creativity moderated by job satisfaction. This type of research used in this research is quantitative. This research was conducted at the Telecommunications Company (Telkom). The sample used in this study amounted to 100. The data used are quantitative data by collecting primary data and secondary data. (1) primary data, in the form of distributing questionnaires in the field to employees of Telecommunications Company (Telkom) and (2) secondary data in this study. are literature, books, literature studies, and online media that can be found in libraries or the internet as supporting information for this research. The analysis used in this research is using smart PLS software to determine the effect of the independent, moderation and dependent variables. The independent variable in this study is authentic leadership (X1), the dependent variable is psychological capital (Y1) and creativity (Y2), while the moderating variable is job satisfaction (Z). The results showed that the authentic leadership variable had a positive and significant effect on Creativity. Authentic leadership has a positive and significant effect on psychological capital. authentic leadership moderated job satisfaction has an influence on creativity. authentic leadership moderated by job satisfaction has an influence on psychological capital. The independent variable in this study is authentic leadership (X1), the dependent variable is psychological capital (Y1) and creativity (Y2), while the moderating variable is job satisfaction (Z). The results showed that the authentic leadership variable had a positive and significant effect on Creativity. Authentic leadership has a positive and significant effect on psychological capital. authentic leadership moderated job satisfaction has an influence on creativity. authentic leadership moderated by job satisfaction has an influence on psychological capital. The independent variable in this study is authentic leadership (X1), the dependent variable is psychological capital (Y1) and creativity (Y2), while the moderating variable is job satisfaction (Z). The results showed that the authentic leadership variable had a positive and significant effect on Creativity. Authentic leadership has a positive and significant effect on psychological capital. authentic leadership moderated job satisfaction has an influence on creativity. authentic leadership moderated by job satisfaction has an influence on psychological capital. The results showed that the authentic leadership variable had a positive and significant effect on Creativity. Authentic leadership has a positive and significant effect on psychological capital. authentic leadership moderated job satisfaction has an influence on creativity. authentic leadership moderated by job satisfaction has an influence on psychological capital. The results showed that the authentic leadership variable had a positive and significant effect on Creativity. Authentic leadership has a positive and significant effect on psychological capital. authentic leadership moderated job satisfaction has an influence on creativity. authentic leadership moderated by job satisfaction has an influence on psychological capital.